Environmental impact studies and its implication on the project investments - Andía V., Walter (2012)
The investment projects involved various means to generate a set of impacts, whether they own the project, social and environmental issues that should be incorporated into the evaluation to determine its viability. The following article has got the principal objetive of analyze the development of environmental impact estudies in relation to the projects and propose a focus on integration between both.